Digital Application-Based Parenting Management to Optimize Parents Educational Interaction with Early Childhood in the Context of Sustainable Education - Luluk Elyana; Soraya Rosna Samta; Mohammad Fauziddin; Maulidya Ulfah (LITERACY : International Scientific Journals of Social, Education, Humanities, 2025)
This study examines the implementation of digital application-based parenting management to optimize educational interactions between parents and early childhood children in Ngaliyan area, Semarang City. The digital era demands transformation of parenting patterns that are more adaptive and integrated with technology. This qualitative research involved 20 active PAUD schools as samples, with data collection techniques through in-depth interviews, observations, and documentation. The results showed that digital parenting applications can improve the quality of parent-child educational interactions by 73%, facilitate child development monitoring, and create learning continuity between home and school. The main challenges include low parental digital literacy (42%), limited internet access (28%), and resistance to changes in traditional parenting patterns (35%). The most effective applications integrate real-time communication features, child development tracking, educational content libraries, and expert consultations. This research recommends developing digital literacy programs for parents, providing adequate technology infrastructure, and continuous training to optimize the use of technology in parenting. Implementation of digital parenting management has proven to support the achievement of sustainable education goals that are responsive to the needs of digital native generations.